PENGENDALIAN KUALITAS PADA PROSES PENERIMAAN BARANG UNTUK MENURUNKAN DEFECT PRODUCT DENGAN PENDEKATAN SIX SIGMA - Annisa Indah Pratiwi; Ragil Yuli Santosa (Industry Xplore, 2021)
The industrial revolution 4.0 has an impact on the progress of a global business, including in Indonesia. One of the companies affected is the Logistics Company. In this research, a logistics company is a company engaged in warehousing and logistics services or 3PL (third party logistics service providers). Based on the research results, it is known that there are five types of products with the highest number of defects in the last six months, namely ER180, IA195, IA120, SL235 and IA220 products. From the Pareto diagram, it is known that the ER180 product is the product that has the highest defect percentage among other products, namely as much as 52%. The processing results obtained an average DPMO value of 185.68538 failures per one million and a sigma level of about 5.06 with a COPQ level of 5-15%. Based on data analysis using Failure Mode and Effect Analysis, there are six types of product defects, namely dented packaging, damaged outer cartons, leaking products, rotten products, inappropriate product dimensions and plain packaging. The main causes of product defects are MHE operators who are not careful, the use of damaged wooden pallets and the lack of lighting in the work area. Based on the analysis using FTA and FMEA, the proposed quality improvement for the company, namely conducting training and training so that employee knowledge and skills increase, selection of pallets according to standards and adding lighting in the work area.